Analysis of the Implemention of Bay’ al-Wafa’ Transactions on Farmers in Pulau Gambar Village Serba Jadi District Serdang Bedagai Regency - Dimas Azhari; Sri Sudiarti; Nursantri Yanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to determine and analyze how the implementation of bay' al-wafa' transactions carried out by farmers in Pulau Gambar Village, Serba Jadi District, Serdang Bedagai Regency. The approach taken is an empirical approach, which is seen from the analysis point of view. This research includes descriptive qualitative research, namely research directed at providing symptoms, facts, or events in a systematic and accurate manner regarding the characteristics of a particular population or area. Data collection techniques used are observation, interviews, and documentation. The results of the study can be concluded that farmers do not understand what bay' al-wafa' is even though it has been practiced by farmers but calls it a pawn agreement. However, in practice, the bay' al-wafa' contract carried out by some farmers has obstacles such as the repurchase tempo that is not in accordance with the contract agreed upon by the seller and the buyer, damage to the goods borne by the seller, and disputes over the rice field area. The bay' al-wafa' transaction has not complied with sharia provisions due to the incorrect mention of the pledge in the transaction and it should have been bay' al-wafa' and damage to the goods that should have been borne by the buyer but borne by the seller.